Factors limiting the exercise tolerance of patients with end-stage renal failure undergoing maintenance haemodialysis - Diesel, Wayne Jonathan (MRC/UCT RU for Exercise and Sport Medicine, 2017)
Exercise tolerance, measured as peak oxygen consumption (VO₂ peak), is very low in patients with end-stage renal failure undergoing maintenance haemodialysis. Due to their associated anaemia and low peak heart rates during maximal exercise it has been argued that the reduced blood oxygen carrying capacity and central cardiovascular limitations are primarily responsible for the poor exercise tolerance of these patients. However, others suggest that peripheral (skeletal muscle) limitations including impaired substrate utilization, muscle weakness caused by peripheral neuropathy and myopathy, malnutrition and general physical deconditioning are responsible for the poor exercise tolerance. The present thesis was therefore designed to study whether central cardiovascular function or anaemia or muscle weakness causes patients with end-stage renal failure to terminate exercise at workrates well below those achieved by healthy controls.